(untitled) (Bangladesh Heart Journal, 2022)
Objective: Vitamin D deficiency is emerging as a new risk factor for various cardiovascular events. Several studies have been done to find out association of vitamin D level with CAD with varying Results. Very few studies, however, have investigated the association between serum vitamin D levels and clinical outcomes in ACS patients thus far. The Objective of this study was to assess the association between serum vitamin D levels and in-hospital complications of AMI patients in Department of Cardiology, Dhaka Medical College Hospital (DMCH), Dhaka. Methods: This was a cross-sectional observational study. We measured serum vitamin D level in AMI (STEMI and NSTEMI) patients (n=198) admitted in Department of Cardiology, DMCH. Patients with normal vitamin D level (e”30 ng/ml) were considered as Group I and patients with low serum vitamin D level (<30 ng/ml) were considered as Group II; and in-hospital complications were evaluated. Results: The study showed that 51% of study subjects of AMI had in-hospital complications; 71.1% patients with low vitamin D level had adverse in-hospital outcome whereas 14.3% patients with normal vitamin D level had AMI complications which was statistically significant (p<0.001). Heart failure and arrhythmias were the most frequently observed complications. The Results of the study demonstrates that the association between low vitamin D level and in-hospital complications after AMI remains statistically significant (p<0.001). Conclusions: Low serum vitamin D level is independently associated with a higher frequency of several in-hospital adverse clinical events including mortality after acute myocardial infarction (STEMI and NSTEMI). Whether low vitamin D levels represent a risk marker or a risk factor in ACS remains to be elucidated. Bangladesh Heart Journal 2022; 37(2): 89-98